2019
DOI: 10.31234/osf.io/432yw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The dual-process approach to human sociality: Meta-analytic evidence for a theory of internalized heuristics for self-preservation

Abstract: Which social decisions are intuitive? Which are deliberative? The dual-process approach to human sociality has emerged in the last decades as a vibrant and exciting area of research. Here, I review the existing literature on the cognitive basis of cooperation, altruism, honesty, positive and negative reciprocity, and (act) utilitarianism. I conclude by introducing a game-theoretical framework that organizes the majority of the empirical regularities. This framework extends Rand and colleagues’ Social Heuristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 403 publications
(512 reference statements)
1
58
0
Order By: Relevance
“…For example, animal research has shown detrimental effects of social deprivation and isolation [2,10,11]. Besides social distancing, the pandemic has resulted in many other changes for adolescents, including possible worry about health of family members, fear of death, financial consequences, and worry about one's future [9,12]. Therefore, social changes in the pandemic should be interpreted in the context of multiple system disruptions [13].…”
Section: Pre-to Peri-pandemic Changes In Mood Empathy and Prosocialmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, animal research has shown detrimental effects of social deprivation and isolation [2,10,11]. Besides social distancing, the pandemic has resulted in many other changes for adolescents, including possible worry about health of family members, fear of death, financial consequences, and worry about one's future [9,12]. Therefore, social changes in the pandemic should be interpreted in the context of multiple system disruptions [13].…”
Section: Pre-to Peri-pandemic Changes In Mood Empathy and Prosocialmentioning
confidence: 99%
“…Future studies should employ large, diverse samples to test the robustness of our findings and to test for individual differences (e.g., in giving). A third limitation is that the COVID-19 pandemic might impact the saliency of other emotions than tension and vigor, such as fear (e.g., fear of death or to lose a loved one), which in turn can affect certain forms of prosociality [12]. Future studies should investigate the effect the COVID-19 pandemic on such emotions and assess their relationship with prosocial tendencies.…”
Section: Strengths Limitations and Recommendations For Future Researchmentioning
confidence: 99%
“…Under the dual-process perspective, the former four determinants stay close with the slow and deliberative process while the emotion is akin to the fast and intuitive cognitive process. In other words, retweeting behavior is propelled by "relying on reason" and "relying on emotion" simultaneously [14,31].…”
Section: Plos Onementioning
confidence: 99%
“…Diederich et al and Guo et al [29,33] found that shorter declines enhanced the framing effect. While time constraints have shown an impact on preferential choice (frequencies) [34][35][36] it seems not to have a significant influence on the amount given in dictator games (for reviews see [37] and [38]). This will be probed here further.…”
Section: Introductionmentioning
confidence: 99%